iHUBUNGAN RIWAYAT AKNE DAN PENGGUNAANMASKER MEDIS DENGAN KEJADIAN MASKNE PADAMAHASISWA FAKULTAS KEDOKTERAN UNIVERSITASPEMBANGUNAN "VETERAN" JAKARTA ANGKATAN 2020 - Reinhart Fikram Imam Akbar (2023)
Abstract: Introduction: Acne is a chronic inflammation originating from the pilosebaceous unit. Since COVID-19 was declared a pandemic, the use of masks as personal protective equipment has increased. Inappropriate use of masks can have adverse effects on skin health. One of the adverse effects of inappropriate mask use is the onset of mask acne (maskne). Methods: This study was conducted using a crosssectional observational study design involving 146 students. The statistical analysis used was the Chi-Square test. Results: There is a significant relationship between previous acne history and the incidence of maskne (P value: 0.029) and there is no significant relationship between the duration of mask use, type of mask, frequency of changing masks with maskne (P value: 0.435; 0.391; 0.815). Conclusion: There is a significant relationship between previous history of acne and the incidence of maskne (P value: 0.029). Keywords: Maskne, Acne, Mask